(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The cultural and architectural heritage of the Amir Temur and Timurid periods has attracted sustained scholarly attention from both Eastern and Western researchers. Early studies, conducted under the Russian Empire, focused on the ancient cities of Samarkand, Afrasiab, and surrounding regions, documenting monuments such as the Gur-e Amir, Bibi-Khanym Mosque, and Shah-i Zinda. Russian archaeologists, Orientalists, and photographers–including N. I. Veselovskiy, S. M. Dudin, V. L. Vyatkin, and V. V. Vereshchagin–systematically recorded architectural, epigraphic, and decorative elements. Research continued during the Soviet period and was complemented by Uzbek scholars. These studies provide critical insights into Timurid architecture, pilgrimage sites, and material culture in Central Asia